The Rate of Return to Investment in Educaton: A Case Study of Lithuania - Potelienė, Simona; Tamašauskienė, Zita (University of Wroclaw. Faculty of Law, Administration & Economics, 2014)
According to human capital theory, people invest in education to accumulate human capital, enhance personal productivity, and in return receive higher life-cycle earnings profiles. Education is a form of human capital investment and accumulation. The formulation and identification of human capital may be quite diverse and usually results in different estimation methods for the rate of return to education. This article is focused on approaches to the measurement of the returns of private investments in human capital in Lithuania. We focused attention on studying human capital investment accumulation through the rate of return on higher education. The aim of the research is to estimate the private rate of return to education in Lithuania and compare calculated data with analogical data in other countries. In the first part of the paper the concept of “human capital” is defined, before estimating the returns to human capital. Further, the research methodology is presented. One of the main ways to calculate the rate of returns to investment in education, which is used in empirical practice, is the full-discounting or elaborate method, which consists in calculating the internal rate of return, and it was this method which was employed. Results indicate that the rate of return for males is relatively higher than for females. The average estimated rate of return to higher education is 13 percent; with the estimated return for females being 12,5 percent; and for males 14,9 percent. After comparing Lithuania‘s and other European countries‘ rates of return on investment in human capital, it is seen that rate of return in Lithuania is similar to that of Spain.
Keywords: Litwa; edukacja; inwestycja